Perceived Parental Support and Adolescents’ Positive Self-Beliefs and Levels of Distress Across Four Countries - Chentsova Dutton, Yulia E.; Choi, In-Jae; Choi, Eunsoo (Frontiers in Psychology, 2020)
Previous research has shown that parental support has beneficial effects on the psychological well-being of adolescents. Going beyond prior research, the present study made distinctions between information, emotional, and financial parental support and examined adolescents from US (N = 1,002), China (N = 1,172), Korea (N = 3,993), and Japan (N = 1,112). The frequency and impact of different types of perceived parental support on adolescents’ positive self-belief and distress levels have been investigated. Consistent with the existing literature, the results showed American adolescents perceived greater emotional and informational support than others, while Chinese, Korean and Japanese adolescents perceived greater tangible support compared to American adolescents. Notably, Chinese adolescents reported higher levels of parental support than other East Asian adolescents. The perceived parental support influenced positive self-beliefs equally across cultural groups, but informational support impacted distress to a greater degree for American adolescents than East Asian adolescents. The implications of the present research are discussed.